The Influence Current Ratio and Debt to Asset Ratio on Return of Assets In PT. Sukabaja Panelindo Utama Jakarta - Gunartin Gunartin; Hamdana Hamdana; Sri Hastutik; Achmad Mamduh (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the Current Ratio and Debt's effect on Asset Ratio on Return on Assets at PT. Sukabaja Panelindo Utama in Jakarta. The method used is explanatory research with a sample of 85 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. This study's results, Current Ratio, significantly affect Return on Assets by 41.3%, hypothesis testing obtained a significance of 0.045 <0.05. Debt to Asset Ratio has a significant effect on Return on Assets of 78.5%; hypothesis testing obtained a significance of 0.001 <0.05. Current Ratio and Debt to Asset Ratio simultaneously affect but not significant to the Return on Assets of 85.0%, hypothesis testing obtained a significance of 0.001> 0.05.